Evaluation of Different Grafting Methods in Promising Kiwifruit Varieties at Lumle, Kaski, Nepal - Khanal, A.; Timilsina, S.; Poudel, N.; Rijal, A.; Khanal, S. (Journal of Agriculture and Environment, 2022)
Kiwifruit is usually propagated by grafting and cutting. Suitable method of grafting in Kiwifruit should be identified to elaborate the commercial production. To evaluate the success rate of scion varieties with different grafting methods in Kiwifruit a study was conducted for two consecutive years 2018 and 2019 at Lumle, Kaski. Five different varieties of Kiwifruit as scion (Allison, Bruno, Hayward Oblong, Hayward Oval and Monty) and three different grafting methods (tongue, veneer and wedge) were used to identify successful method of grafting in Kiwifruit. Grafting was done on January 1st and 2nd in both years. In the first year, shoot length was recorded highest in Hayward Oblong with veneer grafting (96.10cm) whereas shoot diameter was obtained highest in Monty with wedge grafting (6.61mm). Similarly in the second year shoot length was recorded highest in Hayward Oblong with veneer grafting (97.10 cm) and shoot diameter was observed highest in Monty with wedge grafting (6.71mm). In both years, the highest (100%) graft success was recorded in Allison with wedge grafting.